Origin of Radio Emission in Three Nearby Ultraluminous Infrared Galaxies with Signatures of Luminous Buried Active Galactic Nuclei - Takayuki J. Hayashi; Yoshiaki Hagiwara; Masatoshi Imanishi (The Astrophysical Journal)
We report multifrequency Very Long Baseline Array (VLBA) observations at 2.3 and 8.4 GHz of three nearby ultraluminous infrared galaxies, identified via mid-infrared spectroscopic analyses as hosting deeply embedded active galactic nuclei (AGNs). Milliarcsecond-scale observations at both frequencies reveal compact continuum emission in IRAS F00188−0856 and IRAS F01298−0744, accounting for ∼10% of the flux density measured on arcsecond scales. The nondetection in IRAS F00091−0738 and the lower limit on the intrinsic 8.4 GHz brightness temperature of 10 ^6.1 K in IRAS F01298−0744 yield no conclusive evidence of AGN-driven radio emission, whereas the measurement of 10 ^7.8 K in IRAS F00188−0856 confirms an AGN origin. Thus, the mid-infrared AGN classification remains robust, with at least one object exhibiting compact radio emission indicative of AGN activity. We further investigate the high-frequency spectral steepening observed in all three galaxies. In each case, this steepening arises from spectral aging in diffuse kiloparsec-scale emission, which is resolved out by the VLBA observations. One possible explanation for the steepening of the sample is merger-induced particle acceleration. IRAS F00188−0856 exhibits a peaked radio spectrum, characteristic of a young radio source, with the high-frequency steepening attributable to this AGN activity. Consequently, the spectral steepening at high frequencies arises from particles accelerated by merger dynamics or AGN activity.